The Effect of Aerobic Exercise with Nonlinear Pedagogy on Anxiety, Depression, Motor Proficiency and Cognitive Ability of Boys with Attention Deﬁcit Hyperactivity Disorder - Behzad Mohammadi Orangi; Rasoul Yaali; Behrouz Ghorbanzadeh; Paul Loprinzi; Amin Abdalifar (Shiraz University of Medical Sciences, 2021)
Background: This study investigated the effects of the aerobic exercise withmusic on anxiety, depression, motor proficiency, and cognitive ability of boyswith Attention Deficit Hyperactivity Disorder (ADHD).Methods: This is a quasi-experimental study. Participant's comprised aconvenience sample of 36 boys with ADHD. The experimental group (N=18)practiced in non-linear pedagogy (M years=11.32, SD=1.00), whereas the controlgroup (N=18) performed (M years=11.26, SD=0.92) usual school activities in thetraditional method.Results: After participating in the 8-week aerobic training program, motorproficiency, anxiety, depression, working memory, perceptual reasoning, andprocessing speed were improved in the experimental group compared to thecontrol group (p <0.001).Conclusion: Based on these findings, among the ADHD children, incorporatingmusic into sports can affect children's anxiety, depression, motor proficiency,and cognitive ability. Increasing participation by incorporating music into sportssuch as aerobics, can affect children's anxiety, depression, motor proficiency, andcognitive ability.